Mathematical model, technique and computer tools for the process of growing of semiconductors by the bridgman method - Воробець, Георгій Іванович; Рогов, Роман Вікторович; Копач, Олег Вадимович (Eastern-European Journal of Enterprise Technologies, 2015)
As a result of the research, based on the analysis of experimental studies, an adequate physical model for the processes of phase transformation of the CdTe crystal melt was found and its qualitative and quantitative evaluation was carried out. The technique and technical solutions for adaptive control and improvement of the crystal growth process using fuzzy logic methods, which has allowed to predict the critical and incorrect system states, including the lack of crystallization and onset of the supercooled melt condition, and, therefore, save time and money on repeated experiments was proposed. The approaches to creating technical computer tools for intelligent process control, which has allowed to improve the reproducibility of crystal parameters and predict the process flow correctness, as well as reduce the cost of the synthesized material were determined. Already on the synthesis stage, crystal cooling process monitoring has allowed to predict the generation probability of additional monoblocks and assess their characteristic sizes. The synthesis technique and structural and algorithmic solution of intelligent self-adaptive computer tools, built in the process system for improving the control process of furnaces for growing CdTe crystals by the Bridgman method were developed.